1989
DOI: 10.1029/wr025i006p01208
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model of contaminant transport from diffuse sources in saturated porous media

Abstract: An analytical two‐dimensional model of solute transport along a vertical cross section of an aquifer is described. The model extends analytical methods to two‐dimensional dispersive solute transport in a two‐dimensional flow field which until now has been the exclusive province of numerical models. This avoids the very significant problems of numerical instability and numerical dispersion facing the application of numerical transport models at a regional scale. Furthermore, the model is simple and very fast. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…A new formula that is simpler than the former was presented recently by Hsieh (48). More analytical solutions can be found in Li (49), Bear (2) and Sun (8) (58), Chen (59,60), Lowell (61), and Dillon (62) (14) where Sy = specific yield (dimensionless); m = saturated thickness of the aquifer (L); W2 (L/T) and M2 (M/ L2 T) = sink or source; i,j = 1,2. …”
Section: Classical Modelsmentioning
confidence: 99%
“…A new formula that is simpler than the former was presented recently by Hsieh (48). More analytical solutions can be found in Li (49), Bear (2) and Sun (8) (58), Chen (59,60), Lowell (61), and Dillon (62) (14) where Sy = specific yield (dimensionless); m = saturated thickness of the aquifer (L); W2 (L/T) and M2 (M/ L2 T) = sink or source; i,j = 1,2. …”
Section: Classical Modelsmentioning
confidence: 99%
“…Hallberg and Keeney (1993) showed that trends in groundwater quality can also be detected using concentration -depth information, because depth and groundwater age are interrelated under natural flow conditions. This phenomenon is most pronounced in groundwater recharge areas (Raats, 1978;Raats, 1981;Dillon, 1989;Broers, 2002;Broers, 2004). Environmental tracers, such as tritium, are useful for age dating of the groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are based on the assumption that it is possible to average velocity over the whole seepage domain (Freeze et al, 1979, p. 395) or along flow streamlines (Dillon, 1989). In doing so, initial and boundary conditions undergo similar changes or are chosen arbitrarily to permit analytical solutions.…”
Section: Introductionmentioning
confidence: 99%